The Relationship Between Investments and Socio-Economic Indicators in the RA Regions (Quantitative Assessments) - Galstyan, Hamazasp; Tatosyan, Kristine; Badadyan, Gagik; Shahinyan, Mher; Tsatryan, Katrin; Gururyan, Greta («Տնտեսագետ» հրատ․)
Over the years, investments in the Republic of Armenia (RA) regions have mostly positively improved their socio-economic indicators, particularly unemployment and poverty. However, due to investment in regions, impact assessment on the state of socio-economic development of the areas is not carried out, significantly hindering the efficiency of investment management processes. This article aims to evaluate the correlation level between investments and socio-economic indicators in the RA regions using an empirical analytical toolkit. The results of the analysis showed that the RA regions, due to their different levels of economic development, have different volumes of investments per capita. As a result, the high volume of investments per capita in the regions was accompanied by a decrease in poverty and unemployment in the same region, but not in all cases these investments were accompanied by an increase in the number of enterprises. At the same time, during these years, the level of poverty and unemployment did not decrease in the regions that are not distinguished by high investment indicators. In most regions, investments have almost no impact on changes in per capita indicators of various sectors of the economy in the regions.
Keywords: Management